Accreditation performance in area 2: Curriculum design and delivery among undergraduate medical education programmes in Malaysia / Ahmad Soufi Ahmad Fuad - Ahmad Soufi, Ahmad Fuad (2021)
Accreditation exercise of undergraduate medical education in Malaysia involves Malaysian Qualification Agency (MQA) and Malaysian Medical Council (MMC); which was established with the aim of quality assurance. The exercise involves evaluation of medical education programme on nine (9) areas. The present study focuses on Area 2 - Standards of Undergraduate Medical Education, which is curriculum design and delivery. There is paucity of research on conducting accreditation exercise on medical undergraduate medical education in Malaysia. In the present study, analysis was used to identify strengths and improvements of medical curriculum as being reported in accreditation visit reports. Contents in forty-two (n=42) accreditation visit reports of both public and private institutions were analyzed. Items of strength and improvement are identified based on the Area 2 evaluation criteria, which is (i) curriculum design and teaching learning methods, (ii) scientific method, (iii) curriculum content, (iv) ethics and humanities, (v) management of programme, and (vi) linkages with external stakeholders. The findings are then mapped to the six (6) strategies of Harden’s “SPICES” model. It was found that the component of curriculum evaluation in Malaysia is aligned with internationally recognized benchmark for curriculum design and delivery, that is the “SPICES” model. A quantitative analysis was conducted to determine the association between types of institution and accreditation performance. From the analysis, twenty-five (25) programmes (59.5%) received duration of accreditation status less than 5 years period and seventeen (17) programmes (40.5%) received the maximum duration of accreditation status (5-years period). Out of all programmes that received the maximum accreditation period, nine (9) were public institutions (52.9%) and eight (8) are private institutions (47.1%). For programmes that received duration of accreditation period less than 5 years, twenty- iv one (22) were private institutions (88.0%) and only three (3) were public institutions (12.0%). The association was statistically significant where public institutions have a longer duration of accreditation period (p<.01). In terms of Area 2 performance, all twelve (12) public institutions (100%) received Area 2 average score of 76% or more. On the other hand, only nineteen (19) private institutions (65.5%) received Area 2 average score equal or more than 76%. The remaining ten (10) private institutions (34.5%) received Area 2 score less than 76%. There was also a significant association between types of institution with performance in Area 2. Public institutions have higher scores on Area 2 evaluation (p<.05). The present study initiated a pioneering attempt in analyzing MQA/MMC accreditation data for the purpose of academic analysis. Future studies could analyze other areas of evaluation and thus providing a robust analysis. Keywords: accreditation, curriculum evaluation, medical education